Notes on the genus Asiosilis Wittmer, 1977 (Coleoptera, Cantharidae, Silinae) in northern Borneo - Takahashi, Kazuhiro; Dawood, Mahadimenakbar Mohamed (Zootaxa, 2025)
A study on the specimens of the genus Asiosilis (Cantharidae, Silinae) collected by Dr. Haruo Matsuzawa in Sabah, northern Borneo, Malaysia, revealed that it contains 17 species, 10 of which are recognized as new species and are described herein under the name of Asiosilis kiapadensis sp. nov., A. mahuaensis sp. nov., A. babagonensis sp. nov., A. sapulutensis sp. nov., A. kinabaluensis sp. nov., A. takizawai sp. nov., A. inanamensis sp. nov., A. tibouensis sp. nov., A. kliasensis sp. nov., and A. ranauensis sp. nov. The remaining seven previously known species are redescribed. A key to the species of the genus Asiosilis found in Sabah is also provided. Male habitus, antenna, pronotum, and aedeagus of all species are illustrated. The term “basal piece” has been used by Wittmer in his monograph to describe a part of aedeagus; however, we have concluded that the name is inappropriate judging from its origin and have proposed the term “paramere” as an alternative.